Gastric cancer does not affect the expression of atrophy‐related genes in human skeletal muscle. Issue 4 (10th February 2014) - D'Orlando, Cristina; Marzetti, Emanuele; François, Stephanie; Lorenzi, Maria; Conti, Valentina; di, Enrico; Rosa, Fausto; Brunelli, Silvia; Doglietto, Giovan Battista; Pacelli, Fabio; Bossola, Maurizio
ABSTRACT Introduction: We evaluated the gene expression levels of atrogin‐1, MuRF1, myostatin, follistatin, activin A, and inhibin alpha in skeletal muscle samples of patients with gastric cancer and controls. Methods: We studied 38 cancer patients and 12 controls who underwent surgery for gastric adenocarcinoma and benign abdominal diseases, respectively. A biopsy specimen was obtained from the rectus abdominis muscle from all participants. The relative gene expression of atrogin‐1, MuRF1, myostatin, follistatin, activin A, and inhibin alpha was determined by quantitative real‐time polymerase chain reaction analysis. Results: Atrogin‐1 and MuRF1 mRNA expression was similar between cancer patients and controls and was unaffected by the disease stage or the severity of body weight loss. Transcript levels of myostatin and follistatin did not differ between cases and controls and were similar across disease stages and categories of weight loss. Finally, no differences were detected in activin A and inhibin alpha gene expression between cancer patients and controls. Conclusions: In skeletal muscle, the gene expression of atrogin‐1, MuRF1, myostatin, follistatin, activin A, and inhibin alpha is not affected by the presence of cancer. The expression of atrophy‐related genes is unaffected by the disease stage and the degree of weight loss. Muscle Nerve 49:528–533, 2014